Manajemen Ektrakurikuler Futsal Sma Negeri Se- Kabupaten Jepara - Moh Fahmi Khotib; Ibnu Fatkhu Royana; Utvi Hinda Zhannisa (Journal of Physical Activity and Sports (JPAS), 2020)
It is still unknown whether the futsal extracurricular management in Jepara regency is the success of the futsal extracurricular. One of them is determined by management and some schools still do not carry out management functions in extracurricular activities. Therefore, this study aims to determine how the management of futsal extracurricular activities in SMA State Jepara Regency. This research uses qualitative research with a descriptive approach, with the research subjects namely coaches, trainers and students. Collecting data using interview, observation and documentation methods. Data analysis using methods that are carried out continuously with data reduction, data presentation and drawing conclusions. The results of the study are seen from the indicators: (1) Planning is said to have not been programmed properly, seen from the absence of planning in the program being made. Regarding funding, it is not yet detailed in the planning. (2) Organizing is said to be still not competent, seen from the absence of an organizational structure for futsal extracurricular activities. (3) The implementation is said to still experience obstacles in the training process such as the field often collides with other extracurricular activities. The available facilities and infrastructure are inadequate. (4) The supervision is said to have not been maximally carried out because the evaluation is fully left to the trainer. Based on the results of the study, it can be concluded that the extracurricular management of Futsal in SMA State Jepara including planning, organizing, mobilizing and monitoring has not been implemented properly. From the overall suggestion it can be concluded that, to the principal of SMA State in Jepara Regency and the management of the futsal extracurricular that oversees the futsal extracurricular activities of SMA State in Jepara Regency to be able to use the results of this research as input and information in order to improve management performance in order to continue to develop and improve the achievements of futsal extracurricular. Keywords: Management, Extracurricular, Futsal Abstrak Manajemen ekstrakurikuler futsal SMA Negeri se – kabupaten Jepara masih belum diketahui, dimana keberhasilan ekstrakurikuler futsal. Salah satunya ditentukan oleh manajemen dan beberapa sekolah masih belum menjalankan fungsi manajemen dalam ekstrakurikuler. Maka dari itu, penelitian ini bertujuan untuk mengetahui bagaimana manajemen kegiatan ekstrakurikuler futsal SMA Negeri se- Kabupaten Jepara. Penelitian ini menggunakan penelitian kualitatif dengan pendekatan deskriptif, dengan subjek penelitian ini yaitu Pembina, Pelatih dan siswa. Pengumpulan data menggunakan metode wawancara, observasi dan dokumentasi. Analisis data menggunakan metode yang dilakukan secara terus menerus dengan reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian dilihat dari indikator : (1) Perencanaan dikatakan belum terprogram dengan baik dilihat dari tidak adanya perencanaan dalam program yang dibuat. Mengenai pendanaan belum secara terperinci dalam perencanaan. (2) Pengorganisasian dikatakan masih belum berkompeten dilihat dari tidak adanya struktur organisasi kegiatan ekstrakurikuler futsal. (3) Pelaksanaan dikatakan masih mengalami hambatan dalam proses latihan seperti lapangan sering berbenturan dengan ekstrakurikuler yang lain. Sarana dan prasarana yang tersedia kurang memadai. (4) Pengawasan dikatakan belum maksimal dilakukan karena evaluasi sepenuhnya diserahkan kepada pelatih. Berdasarkan hasil penelitian dapat disimpulkkan bahwa Manajemen Ektrakurikuler Futsal SMA Negeri se- Kabupaten Jepara meliputi perencanaan, pengorganisasian, penggerakan dan pengawasan belum bisa terlaksana dengan baik. Dari saran keseluruhan dapat disimpulkan bahwa, kepada kepala sekolah SMA Negeri se- Kabupaten Jepara dan kepengurusan ektrakurikuler futsal  yang menaungi ekstrakurikuler futsal SMA Negeri se- Kabupaten Jepara untuk dapat menggunakan hasil penelitian ini sebagai bahan masukan dan informasi dalam rangka meningkatkan kinerja manajemen agar terus mengembangkan dan meningkatkan prestasi dari ekstrakurikuler futsalnya. Kata kunci : Manajemen, Ektrakurikuler, Futsal.